Community Education in the Perspective of Student Scientific Works 2012-2022 - Elih Sudiapermana; Deti Nudiati (Universitas Negeri Padang, 2023)
The thesis, which is one of the scientific research activities, aims to find answers to a problem in a scientific manner. In educational thesis, the research activity is directed towards understanding various issues and phenomena in education, across all educational levels, and in every aspect. Thus, ideally, the thesis in community education should use social phenomena and issues as the source of its research problems. This study aims to provide an empirical overview of how social issues are used as research problems in community education thesis and how these issues have evolved in society over the past 10 years (2013-2022), as well as any possible correlations between the two. The research was conducted using a descriptive quantitative approach on 492 community education student thesis titles. The results show that the three main social issues in the thesis are the quality of education, human resource quality, and economic and welfare disparities, and these three major issues have different focuses compared to national social issues during the 10-year period. The discussion trend in the thesis is consistent with the basic concept of community education that examines the philosophy of education that underlies school society, encouraging opportunities for members of society, including individuals, schools, businesses, and public or private organizations, to become partners in meeting community needs. However, compared to national issues, the correlation between the social issues researched by students is very weak, and this is a challenge for community education stakeholders to minimize the gap between academic discussion and social phenomena in society.